Gastroesophageal reflux disease may causally associate with the increased atrial fibrillation risk: evidence from two-sample Mendelian randomization analyses - Wang, Lei; Lu, Yi Wei (Frontiers in Cardiovascular Medicine, 2024)
Background The risk of atrial fibrillation (AF) is increased in individuals with gastroesophageal reflux disease (GERD), according to observational research. The causal significance of this association is still unclear. This study sought to assess GERD's role as a potential contributing factor in AF. Methods With the use of a two-sample Mendelian randomization (MR) technique, we assessed the causal relationship between GERD and AF. The association of genetic variants with GERD was examined using data from a recent genome-wide association study (GWAS) that included 602,604 people. Data on the association between genetic variations and AF was obtained from a second GWAS with 1,030,836 participants. The effect sizes were examined based on the inverse-variance weighted method. Additional statistical techniques, including MR-Egger, simple mode, weighted mode, MR Pleiotropy Residual Sum, outlier, and weighted median were used in the sensitivity analysis. Results MR analyses in inverse-variance weighted models, using 76 single nucleotide polymorphisms (SNPs) as markers, revealed a relationship between genetically predicted GERD and a greater AF incidence [odds ratio (OR): 1.165, 95% CI 1.102–1.231; P = 7.637 × 10−8]. According to MR-Egger, there was no evidence of gene pleiotropy that could be found (intercept = 0.003, P = 0.581). The findings of the sensitivity study, which used several MR methods, were found to be reliable. Conclusion The MR analysis revealed a correlation between GERD and increased AF incidence, supporting the idea that treating patients with GERD as early as possible might reduce their chance of developing AF.